Quantitative Runge approximation and inverse problems - Rüland, Angkana; Salo, Mikko (International mathematics research notices, 2019)
In this short note, we provide a quantitative version of the classical Runge approximation property for second-order elliptic operators. This relies on quantitative unique continuation results and duality arguments. We show that these estimates are essentially optimal. As a model application, we provide a new proof of the result from [8], [2] on stability for the Calderón problem with local data.